Performance testing with JMeter : test web applications using Apache JMeter with practical, hands-on examples - Erinle, Bayo (Community experience distilled., 2015)
This book is great for developers, quality assurance engineers, testers, and test managers new to Apache JMeter, or those who are looking to get a good grounding in how to effectively use and become proficient with JMeter. No prior testing experience is required.